ARTI TANGISAN BAYI - hasibuan, lily zefrina; harahap, afriani; dalimunthe, rahmah yasrah (Nunchi : Islamic Parenting Journal, 2023)
Crying is the main communication medium for babies in presenting their desires to the environment, especially to mothers or babysitters. Some conditions that can cause babies to cry are when the baby feels hungry, uncomfortable, sleepy, in pain, and so on.Â  This research is a type of qualitative research that uses literature research methods. The purpose of this study was to find out what exactly the baby's cry meant. It is through crying that the baby conveys his wish that the mother or babysitter can fulfill his wish. If the mother or babysitter is wrong in fulfilling the baby's wishes, misunderstands the baby's wishes, then the baby will continue to cry until his wishes are fulfilled. Each cry can exhibit certain characteristics by acoustic signals that are classified based on the cause of the baby's crying. The development of infant speech increases with age and development of the baby. Environmental conditions and infant comprehension that will help in the learning process of baby speech, for example when the baby is less than 1 month old the intensity of crying will be higher than that of babies aged 9 months.